Translation, Psychometric and Concept Analysis of the Occupational Balance-Questionnaire Based on a Turkish Population - Bahadır, Zeynep; Yaran, Mahmut; Özkan, Esma; Ekici, Gamze; Huri, Meral; AKEL, BURCU SEMİN (Taylor & Francis Inc., 2021)
Occupational balance is a crucial concept in occupational therapy, accepted as a key component of health and well-being. The Occupational Balance-Questionnaire (OB-Quest) is designed as a standardized instrument to assess occupational balance. This study investigated the validity and reliability of the OB-Quest Turkish, which consisted of translation, cross-cultural adaptation, and analysis psychometric properties phases. The factor structure of the OB-Quest indicated a good model fit. The criterion-related validity showed a positive correlation with Beck Depression Inventory and a negative correlation with the 12-item Short Form Survey. The OB-Quest-Turkish showed questionable internal consistency and an excellent correlation between test-retest.
Keywords: Occupational Balance; Psychometrics; Reliability and Validity; Self-report